Ground temperature variability in Poznań (2011–2020) - Szyga-Pluta, Katarzyna (Quaestiones Geographicae, 2022)
The manuscript concerns the analysis of the ground temperature in Poznań in the years 2011–2020. Data generally available on the Institute of Meteorology and Water Management – National Research Institute (IMGW-PIB) website were used. The ground temperature was measured at five depths: 5 cm, 10 cm, 20 cm, 50 cm and 100 cm. The highest variability of ground temperature occurred in summer and the lowest in winter. The ground temperature was closely correlated mainly with air temperature, but also with insolation and water vapour deficit. There is a statistical increase in the air temperature in Poznań – the trends at the whole soil profile are positive although not statistically significant.